Biological Individuality in Scientific Practice: Individuation Criteria and Epistemic Goals (Culturas Científicas, 2021)
Biology uses multiple criteria to individuate biological phenomena. Monistic approaches propose that we should arbitrate between that diversity and define unique criteria of individuality, that is, unique ways of counting individuals in biology. Pluralism, on the other hand, argues that we should not restrict the study of individuality to unique conceptions, recognizing different types of individuals. In this article I will analyze how some monistic and pluralistic approaches face the plurality of individuation criteria used by scientific practice. Following the recent epistemological and pragmatic approaches in the philosophy of biological individuality, I will argue why the diversity of individuations is usually not a problem for biology and why it contributes to our knowledge of the biological world. The general conclusion will be that we require multiple ways to individuate nature in order to fulfill the various epistemic goals of biology, a task that monistic approaches do not usually make visible.
Keywords: Biological Individual; Plurality; Pluralism; Monismo